EVALUASI KOMPONEN PERTUMBUHAN, KOMPONEN HASIL, DAN KUALITAS AROMA TIGA VARIETAS LOKAL PADI GOGO AROMATIK SEBAGAI RESPON TERHADAP TINGKAT SALINITAS - Marsel I. Tse; IG.B. Adwita Arsa; Antonius S.S. Ndiwa; Roddialek Polo; Yuhanes Umbu Iburuni; Antonius S. Suban Hali (JURNAL AGRISA, 2022)
This study aimed to determine the effect of soil salinity level on growth and yield components and rice-aroma quality of three local varieties of aromatic upland rice. The research was arranged in a split-plot design laid out in a completely randomized design with three replications. The main plot was the soil salinity level (S) which consisted of four levels, namely, 1.0, 2.0, 3.0, and 4.0 g/kg soil respectively. The sub-plots were the local varieties of aromatic upland rice namely: Pare Hunga Kuhi, Pare Kiku Lapale, and Pare Panenggo Ate. Parameters observed included growth components, yield components, grain yield, and quality of rice aroma. Data were analyzed by analysis of variance and the HSD 5% test. The results showed that the soil salinity level treatment siginificantly affected plant height at 12 and 16 weeks after planting (WAP), the number of tillers (16 WAP), the grains weight, the number of panicles, the number of grain panicles, and the percentage of unfilled grains. The treatment varieties treatment was significantly influence in plant height (4 and 8 WAP), in the number of leaves (16 WAP), in whole leaves area (16 WAP), and in the flowering date, however among those there was no interaction effect between soil salinity and varieties. The best yield and grain yield components were apparently at soil salinity level of 1.0 g and 2.0 g NaCl. kg soil-1. On the other hand the soil salinity level until 3.0 g NaCl. kg soil-1 showed increased in the rice aromatic score (2AP).